Noble metal nanoparticles applications in cancer - Conde, João (2020)
Nanotechnology has prompted new and improved materials for biomedical applications with particular emphasis in therapy and diagnostics. Special interest has been directed at providing enhanced molecular therapeutics for cancer, where conventional approaches do not effectively differentiate between cancerous and normal cells; that is, they lack specificity. This normally causes systemic toxicity and severe and adverse side effects with concomitant loss of quality of life. Because of their small size, nanoparticles can readily interact with biomolecules both at surface and inside cells, yielding better signals and target specificity for diagnostics and therapeutics. This way, a variety of nanoparticles with the possibility of diversified modification with biomolecules have been investigated for biomedical applications including their use in highly sensitive imaging assays, thermal ablation, and radiotherapy enhancement as well as drug and gene delivery and silencing. Here, we review the available noble metal nanoparticles for cancer therapy, with particular focus on those already being translated into clinical settings.